Management of Hemostasis for Pediatric Patients on Ventricular-Assist Devices - Adachi, Iki; Kostousov, Vadim; Hensch, Lisa; Chacon-Portillo, Martin A.; Teruya, Jun (Seminars in Thrombosis and Hemostasis, 2018)
Ventricular-assist devices (VADs) have seen increased utilization in the pediatric population. Formerly, this therapeutic modality was limited to only the pulsatile VAD, EXCOR (Berlin Heart GmbH). However, the continuous flow VAD devices, HeartMate II (Abbott Inc.) and HeartWare (Medtronic Inc.), are now increasingly used in this population. Postoperatively, VAD patients are acutely anticoagulated using unfractionated heparin, often beginning 24 to 48 hours after VAD placement. Once the patient is stabilized and ready to transition to a lower acuity or outpatient setting, low-molecular-weight heparin or warfarin therapy may be instituted. Also, because of the risk for thrombotic and thromboembolic complications, antiplatelet strategies are employed using medications such as aspirin, clopidogrel, or dipyridamole. Platelet-rich plasma or whole blood platelet aggregation studies, platelet function analyzer-100 (Siemens), VerifyNow (Accriva Diagnostics), or thromboelastography platelet mapping (Haemonetics) may be used to help monitor antiplatelet effects, though the interpretation of the strength of the antiplatelet effect remains difficult. Care must be taken to monitor the hematologic complications of VAD, including acquired von Willebrand syndrome, which increases the risk for bleeding, and intravascular hemolysis, which increases the risk of thrombosis. Appropriate device placement and anticoagulation management are imperative to help avoid neurological dysfunction and ischemic stroke, the most devastating potential complications of VAD therapy. As our experience grows, we continue to gain an increased understanding of the management of anticoagulation, need for antiplatelet medication, and appropriate monitoring for these critical patients.
Keywords: ventricular-assist device; acquired von Willebrand syndrome; antiplatelet; monitoring; anticoagulant; hemolysis